PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN SEKTOR PERDAGANGAN JASA DAN INVESTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Agren Bunga; Maria Elerina Douk Tunti (Universitas Nusa Cendana, 2020)
The study was conducted to determine the effect of financial performance measured using the current ratio, total asset turnover, debt to equity ratio, return on equity, and earnings per share on stock returns in services and investment trading sector companies listed on the Indonesian stock exchange. This research is quantitative research. The sampling technique using purposive sampling and obtained as many as 118 companies. The data analysis technique used is multiple regression analysis, classic assumption test, T test, F test, and determination coefficient test. The results of the T test show that partially, the current ratio, return on equity, and earnings per share have a significant effect on stock returns. Partially, total asset turnover and debt to equity ratio do not affect stock returns. The F test results show that the current ratio, total turnover assets, debt to equity ratio, return on equity, and earnings per share simultaneously influence stock returns. The results of determination coefficient concluded that 24.9% of stock returns can be explained by financial performance, and the remaining 75.1% is influenced by other factors outside of research. Keywords: financial performance, current ratio, total asset turnover, debt to equity ratio, return on equity, earnings per share, and stock returns